ChemInform Abstract: A Catalytic Diastereoselective Formal [5 + 2] Cycloaddition Approach to Azepino[1, 2‐a]indoles: Putative Donor‐Acceptor Cyclobutanes as Reactive Intermediates. Issue 17 (April 2015) - Shenje, Raynold; Martin, M. Cynthia; France, Stefan
Abstract Alkyl‐substituted terminal double bonds [e.